Dose–Response Relation between Tea Consumption and Risk of Cardiovascular Disease and All-Cause Mortality: A Systematic Review and Meta-Analysis of Population-Based Studies. Issue 4 (19th February 2020) - Chung, Mei; Zhao, Naisi; Wang, Deena; Shams-White, Marissa; Karlsen, Micaela; Cassidy, Aedín; Ferruzzi, Mario; Jacques, Paul F; Johnson, Elizabeth J; Wallace, Taylor C
ABSTRACT: Tea flavonoids have been suggested to offer potential benefits to cardiovascular health. This review synthesized the evidence on the relation between tea consumption and risks of cardiovascular disease (CVD) and all-cause mortality among generally healthy adults. PubMed, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, Food Science and Technology Abstracts, and Ovid CAB Abstract databases were searched to identify English-language publications through 1 November 2019, including randomized trials, prospective cohort studies, and nested case-control (or case-cohort) studies with data on tea consumption and risk of incident cardiovascular events (cardiac or peripheral vascular events), stroke events (including mortality), CVD-specific mortality, or all-cause mortality. Data from 39 prospective cohort publications were synthesized. Linear meta-regression showed that each cup (236.6 mL)  increase in daily tea consumption (estimated 280 mg  and 338 mg  total flavonoids/d for black and green tea, respectively) was associated with an average 4% lower risk of CVD mortality, a 2% lower risk of CVD events, a 4% lower risk of stroke, and a 1.5% lower risk of all-cause mortality. Subgroup meta-analysis results showed that the magnitude of association was larger in elderly individuals for both CVD mortality ( n  = 4; pooled adjusted RR: 0.89; 95% CI: 0.83, 0.96; P  = 0.001), with large heterogeneity ( I 2  = 72.4%), and all-cause mortality ( n  = 3; pooled adjusted RR: 0.92; 95% CI: 0.90, 0.94; P < 0.0001; I 2  = 0.3%). Generally, studies with higher risk of bias appeared to show larger magnitudes of associations than studies with lower risk of bias. Strength of evidence was rated as low and moderate (depending on study population age group) for CVD-specific mortality outcome and was rated as low for CVD events, stroke, and all-cause mortality outcomes. Daily tea intake as part of a healthy habitual dietary pattern may be associated with lower risks of CVD and all-cause mortality among adults.